Aspekty Geopolityki w Formule 1 .......... 195 (Oblicza dyplomacji, 2025)
THE GEOPOLITICS OF FORMULA 1The aim of the paper is to prove the thesis that the current goals and activities of Formula 1 (F1) are dependent on the ongoing and multidimensional geopolitical processes. After a brief description of the rules of this sport, the Author focuses on presenting external influences on the most important structures of F1. A crucial point of the paper is enhancing the decisions that are being made based on contemporary geopolitical processes by F1 and the FIA, as the organization managing F1. The author also presents the essence of the prestige of this racing series, which is important for the host countries. The most important part of this paper is showcasing the objectives of F1 and its goals as an organization, the process of building the image both by the hosts, including sportswashing, and the teams and drivers, as well as showing the alleged geopolitical reasons for the appearance of selected circuits in the latest F1 calendars. The Author does not present the paper from a sport’s point of view. A concise description provides the readers with only the basic knowledge about this discipline. The theme of the text is geopolitics and its aspects that are present in contemporary F1. Furthermore, the Author is convinced that a multidimensional analysis of the processes occurring in this sport allows for the drawing of promising conclusions that can further develop the thesis, as well as indicate predictions regarding the path of development that F1 may choose in the future.